Factors Influencing the Acceptability of Nominal, Non-nominal, and Anonymous HIV Testing Options Among Young Men Living in Vancouver, Canada: A Qualitative Study. (12th January 2023) - Lowik, A.J.; Prangnell, Amy; Carson, Anna; Wong, Jason; Knight, Rod
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Individuals unaware of their HIV seropositive status continue to represent a key "driver" of the HIV epidemic. Strategies to improve initiation into the HIV treatment cascade, including among young men, are required. This study assesses the acceptability of three HIV testing options among young cisgender men living in Vancouver, British Columbia. Using a modified grounded theory approach, we conducted semi-structured interviews with 45 young cisgender men ages 18–30 years to identify the factors influencing the acceptability of diverse HIV testing approaches. Participants ascribed value to non-nominal testing as a means of providing a secure pathway to HIV-related care for those who test positive while also safeguarding privacy. Anonymous HIV testing was problematized by participants as potentially creating difficulty in accessing ongoing HIV-related care. Most participants preferred non-nominal testing. Nevertheless, based on principles of equity, we argue that anonymous access to one's serostatus should be available, especially within a criminalized context.